MPS 14-09 PHYSIOLOGICALLY INDIVIDUALISED THERAPY FOR RESISTANT HYPERTENSION IN AFRICA: PRELIMINARY REPORT. (September 2016) - Rayner, Brian; Jones, Erika; Akintunde, Adeseye; Nondi, Justus; Gogo, Kennedy; Spence, David
Abstract : Objective: To determine whether individualized therapy for resistant hypertension based on physiological determinants of salt and water retention will achieve better control of blood pressure, compared to guideline-based care, among black Africans. Design and Method: Patients with resistant hypertension who attend Hypertension clinics in three African medical centres were randomized to usual care versus physiologically individualized therapy. Data were gathered on patients at randomization, one, six and twelve months. Data were collected on plasma renin and aldosterone levels, blood pressure, medications, investigations, visits, adverse drug effects and outcome events. Local ethics committees approved the study and patients gave signed informed consent. Patients were randomized to usual care versus therapy according to renin and aldosterone: aldosterone antagonist for low renin/high aldosterone; amiloride for low renin/low aldosterone; ARB for high renin/high aldosterone. Other medications were added according to blood pressure response. The primary outcome was the proportion of patients achieving target blood pressure at one year on the two strategies. Secondary outcomes were the number of visits, number of medications, adverse effects of medications and adverse outcomes such as decline in GFR, hypokalemia, hyperkalemia, and admission to hospital with cardiovascular outcomes such as stroke and heart failure. Data were analysed with SPSS. Results: One hundred and two patients were enrolled. There were no differences in baseline characteristics between the patients that received standard guideline based care and those that received individualised care. BP targets (< 140/90 mmHg) were reached in 25% for SBP and 43% for DBP in the standard care arm and 75% and 65% in the physiological care arm at one year, p < 001 for SBP and P = 0.024 for DBP. The BP drop was 19 ± 25/5 ± 18 in the standard care arm and 29 ± 25/5 ± 16 in the physiological care arm (NS). Conclusions: Individualised therapy for hypertension increased the proportion of patients reaching target blood pressures at one year in these preliminary data.